Characterization of a Deep Sea Bacillus toyonensis Isolate: Genomic and Pathogenic Features - Luo, Jing-chang; Long, Hao; Zhang, Jian; Zhao, Yan; Sun, Li (Frontiers in Cellular and Infection Microbiology, 2021)
Bacillus toyonensis is a group of Gram-positive bacteria belonging to the Bacillus cereus group and used in some cases as probiotics or biocontrol agents. To our knowledge, B. toyonensis from the deep sea (depth >1,000 m) has not been documented. Here, we report the isolation and characterization of a B. toyonensis strain, P18, from a deep sea hydrothermal field. P18 is aerobic, motile, and able to grow at low temperatures (4°C) and high concentrations of NaCl (8%). P18 possesses a circular chromosome of 5,250,895 bp and a plasmid of 536,892 bp, which encode 5,380 and 523 genes, respectively. Of these genes, 2,229 encode hypothetical proteins that could not be annotated based on the COG database. Comparative genomic analysis showed that P18 is most closely related to the type strain of B. toyonensis, BCT-7112T. Compared to BCT-7112T, P18 contains 1,401 unique genes, 441 of which were classified into 20 COG functional categories, and the remaining 960 genes could not be annotated. A total of 319 putative virulence genes were identified in P18, including toxin-related genes, and 24 of these genes are absent in BCT-7112T. P18 exerted strong cytopathic effects on fish and mammalian cells that led to rapid cell death. When inoculated via injection into fish and mice, P18 rapidly disseminated in host tissues and induced acute infection and mortality. Histopathology revealed varying degrees of tissue lesions in the infected animals. Furthermore, P18 could survive in fish and mouse sera and possessed hemolytic activity. Taken together, these results provide the first evidence that virulent B. toyonensis exists in deep sea environments.